Proposal for a digital health platform: Supporting a regional innovation ecosystem from the quadruple helix - Nodari, Cristine Hermann; Nunes, Moema; Curth, Marcelo; Monzon, Daiana de Leonço (International Journal of Innovative Research and Scientific Studies, 2025)
This article proposed a digital health platform for developing and supporting a regional health ecosystem from the perspective of the quadruple helix. This objective was achieved based on studies on innovation ecosystems and the quadruple helix model. The research uses design science research to create two artifacts that emphasize the practical applicability of the study. A field diary was used to collect data further to deepen the understanding of the regional ecosystem; secondary analysis of online documents and interviews were also used. The study developed two artifacts, one of which was a digital health platform, and, as a second artifact, the need for collaborative and constant action between university-business-government-society was also perceived. The creation of a digital health platform based on the quadruple helix model indicates the support and development of mechanisms for identifying parts of a regional innovation ecosystem, where the interaction between the different actors generates synergies for developing practical solutions focused on users' needs.